Implementation of the E-TWI Application for Legal Protection, Prevention of Violations and Jobseeker in Indonesian Migrant Workers - Herri A. B; Sunarti; Karina F.L.S (International Journal of Research in Vocational Studies (IJRVOCAS), 2023)
TKI complains about various problems, namely being sent home, salaries not being paid, termination of employment before the work agreement ends, overstaying, and TKI not leaving. For this reason, it is necessary to monitor the progress of migrant workers while working abroad as well as the problems that occur in the government and among migrant workers themselves. Violations and prevention can be avoided if migrant workers know the laws, social and culture abroad, especially in Taiwan. On the other hand, TKI must know how to submit complaints to the Indonesian government, foreign governments, and closest government representatives. The problem that most often occurs is that the company terminates employment without terminating the contract, for this reason, we need an application that can help us find work before being sent home because the cost of becoming a migrant worker is very expensive. This has resulted in many illegal migrant workers, especially in Taiwan. This research targets the realization of a product in the form of the E-TWI application: Legal Protection, Prevention of Violations, and Job Search for Migrant Workers in Taiwan. Apart from that, this service product also aims to improve the quality of preventive treatment and legal protection for migrant workers in Tainan, Taiwan, reduce the budget figure for migrant workers, especially FKKBWIT members, and reduce the number of TKI who are forced to flee due to natural disasters accident lose their job. The E-TWI application: Legal Protection, Prevention of Violations and Job Search for Taiwanese Migrant Workers has features: reporting, complaints, legal and violation education, posting job vacancies to fellow workers, searching for work agents, and consulting legal and employment services.